Application of Water Quality Index in Assessing water Quality: A Case Study of the Shatt Al Arab River. - Hadi Hamza, Zuhal Abdul (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This investigation pertains to the evaluation of water quality in the Shatt Al-Arab River, located in the Basrah province of southern Iraq, from 2017 to 2022. Its quality should be assessed regularly, and the condition of water resources should be maintained accordingly. The most common analytical method for describing and assessing general water quality is the Water Quality Index (WQI). Various physicochemical parameters like pH, total dissolved solids, total hardness, calcium, magnesium, chloride, and total alkalinity are considered for the present study. The Weighted Arithmetic Water Quality Index Technique is used to evaluate these data. For checking the portability of the parameters within the acceptable limit, WHO is adopted. According to the study mentioned above, the quality has been found to be very low compared to the WQI value. It is also observed that the water was found unsuitable for drinking purposes, and it is considered harmful to human health; therefore, it requires some kind of processing before use. This study will be beneficial to policymakers for identifying and providing details about water quality in the form of a specific value.